(untitled) (World Science, 2023)
Any war influences the mental and physical health of inhabitants of the country suffering from aggression. Anxiety is one of the mental disorders with increased prevalence during the war. A close relationship between anxiety and carbon dioxide concentration in the human body was revealed. There is no doubt about the pivotal role of the later in vascular tone control and the appropriate functioning of the endothelium. This paper presented case series of three female patients with similar complaints exacerbated after a stressful situation (bombing) in the period of the Russian-Ukrainian War. In addition to routine investigational methods (anamnesis taking, physical examination, electrocardiography, and transthoracic echocardiography at rest), Hamilton Anxiety Score and capnometry were used. The trend of drastically decreased end-tidal concentration of carbon dioxide and mild to severe anxiety levels was noticed. We consider there is a connection between the severity of anxiety and end-tidal concentration of carbon dioxide that indirectly reflects the possible endothelial dysfunction. Therefore, taking into consideration patho-mechanisms and pathology data, using differential pathogenetic methods of surgical invasion and computer monitoring of post-operative period we managed to decrease mortality in severecerebro-cranial traumas to 29-30% comparing to pre computer periods 36-38 % and comparing to data of other clinics 35-45%.